Gambaran Akseptor Sekaitan Dengan Kontrasepsi Suntik Di Klaten - Dwi Retna Prihati; Ni Wayan Yeni M; Umi Nadhirotun Nikmah (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Background: Injection contraception is a "primadonna" contraception in the sense that it is chosen by most family planning acceptors in Indonesia. Hormonal acceptor 73.08%. Characteristics of respondents and all things related to acceptors such as knowledge, role of midwives, support, and others are important points to ensure the welfare of acceptors so that complications from various complications arise. The purpose of this study was to determine the description of acceptors related to injection contraception in Klaten. Method: The method used is survey. Total sample of 139 people. Results: The study results of respondents aged < 35 years were 59.7%, using contraception ≤ 2 years as much as 66.9%. has no contraindications to the use of hormonal contraception which is 94.9%. Conclusion: Respondents chose injection contraception because of their own choice of 80.6%, respondents knew about active ingredients in injection contraception as much as 96.4%, respondents knew about the side effects of injection contraception 50.4%, respondents stated that they could use continuous injection contraception for life 34, 5%, respondents did not receive information about injectable contraception from midwives at the first visit of 65.5%, respondents knew contraindications to injection contraception 77.7%, respondents said midwives did not ask complaints every time they visited 71.3%, respondents stated midwives provide health counseling at 65.5% each time, respondents say midwives do not do head to toe examinations including breasts at 67.6, respondents do not plan to replace other contraceptives by 84.9%.